Tax evasion of high-net-worth individuals / Siti Hawa Shuid - Shuid, Siti Hawa (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The term high-net-worth individuals (HNWIs) is commonly interpreted as individuals who have accumulated net worth or wealth that positions them at the top of the wealth scale within a country or even on a global scale (Mc Laughlin & Buchanan, 2017). The concept of net wealth is related to combining the value of financial assets and tangible assets owned by individuals and their immediate families while deducting their financial debts. Specifically, Knight Frank (2023) defined HNWIs as an individual with a net worth equal to or exceeding US$1 million. There is another term for this superrich individual, which is ultra-high-net-worth individuals (UHNWIs), which can be defined as an individual with a net worth equal to or exceeding US$30 million. However, considering Malaysia's standpoint, the Securities Commission of Malaysia (2021) characterized the HNWIs as an individual whose collective net investment portfolio, whether held personally or jointly with their spouse, exceeds RM1 million or the equivalent amount in foreign currencies.